Peacemaking and peacebuilding in South Africa : the National Peace Accord, 1991-1994 - Carmichael, Liz (James Currey, 2022)
Examines the creation and implementation of South Africa's National Peace Accord and this key transitional phase in the country's history, and its implications for peace mediation and conflict resolution.--